Cardiovascular safety of evogliptin in patients with type 2 diabetes: A nationwide cohort study. Issue 6 (10th February 2021) - Park, So‐Hee; Jeong, Han Eol; Oh, In‐Sun; Hong, Sang‐Mo; Yu, Sung Hoon; Lee, Chang Beom; Shin, Ju‐Young
Abstract: Aim: To assess whether the use of evogliptin, a novel dipeptidyl peptidase‐4 inhibitor (DPP‐4i), was associated with an increased risk of cardiovascular events compared with glimepiride in patients with type 2 diabetes (T2D). Methods: We conducted a population‐based cohort study using South Korea's nationwide healthcare database from 1 January 2014 to 31 December 2018. We identified a base cohort of patients with T2D who newly initiated metformin monotherapy, from which we identified a study cohort of patients who either added or switched to glimepiride or DPP‐4is (including evogliptin). Patients were followed up from initiation of DPP‐4is or glimepiride until the earliest of either outcome occurrence or 31 December 2018. Our primary outcome was hospitalization or an emergency visit for cardiovascular events, a composite endpoint comprised of cerebrovascular events, heart failure, myocardial infarction, transient ischaemic attack, angina pectoris and revascularization procedures; secondary outcomes were the individual components of the primary outcome. A multivariable Cox proportional hazards model was used to estimate adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) for the risk of study outcomes associated with evogliptin compared with glimepiride. Results: Our base and study cohorts had 317, 307 and 128, 788 patients, respectively, of which 100, 038 were DPP‐4i users (2946 were evogliptin users) and 28, 750 were glimepiride users within the study cohort. The median follow‐up was 195 days for evogliptin and 113 days for glimepiride users. Compared with glimepiride, evogliptin was associated with a reduced risk of the primary outcome (aHR 0.67, 95% CI 0.48–0.95) and cerebrovascular events (aHR 0.41, 95% CI 0.22–0.78) but showed non‐significant associations for myocardial infarction (aHR 0.63, 95% CI 0.27–1.46), heart failure (aHR 0.35, 95% CI 0.09–1.47), transient ischaemic attack (aHR 0.23, 95% CI 0.03–1.72) and angina pectoris (aHR 1.35, 95% CI 0.82–2.21). Conclusions: Findings from this population‐based cohort study provide novel real‐world evidence that the use of evogliptin, compared with glimepiride, did not increase the risk of cardiovascular events, including cerebrovascular events, myocardial infarction, heart failure, transient ischaemic attack and angina pectoris.